Implementasi Penilaian Autentik Kurikulum 2013 pada Mata Pelajaran Pendidikan Agama Kristen di SMP Negeri 1 Motoling - Regina Reine Timporok; Benny Binilang; Cyrus Lalompoh (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to identify, analyze and describe: (1) Implementation of 2013 Curriculum Authentic Assessment in Christian Religious Education Subject at SMP Negeri 1 Motoling; (2) Supporting factors for the Implementation of Authentic 2013 Curriculum Assessment in Christian Religious Education Subject at SMP Negeri 1 Motoling; (3) Inhibiting factors for the Implementation of Authentic Assessment of Curriculum 2013 on Christian Religious Education Subject at SMP Negeri 1 Motoling; (4) Efforts made by school to overcome obstacles in the implementation of the 2013 Curriculum Authentic Assessment on Christian Religious Education Subject at SMP Negeri 1 Motoling. This research is a qualitative research with the triangulation method that is carried out at SMP Negeri 1 Motoling in 2020. The Data were collected through observation, interview and documentation study. From the analysis and interpretation of the data, it is indicated that: (1) The implementation of authentic assessments carried out by teacher is very much needed in supporting active and creative children's learning achievement; (2) The teacher must know what attitude to take in facing obstacles in the learning process; (3) Cooperation between school principals, teachers, parents and even students become the spearhead in the achievement of learning outcomes. From these findings, it is recommended for teachers in general who do not know well about authentic assessment and especially for Christian Religious teachers in applying authentic assessment.